Strategi Pembelajaran Fikih dengan Pendekatan Problem Based Learning di Madrasah Aliyah - Lora Endrita (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
This study aims to analyze the application of the Problem Based Learning method in Islamic Jurisprudence learning at MAN 1 Solok, and to identify supporting and inhibiting factors in its implementation. The research method used is a qualitative approach with a case study research type. Problem Based Learning is applied to improve students' creativity in thinking and building solidarity in making decisions. The results of the study indicate that the application of the Problem Based Learning method is able to form students who are creative, critical, able to solve problems through decision making based on various opinions, and respect differences. This method is also effective in increasing students' activeness, collaboration, and understanding of Islamic Jurisprudence material. Supporting factors for the implementation of this method include the availability of facilities and infrastructure, teacher creativity, and a conducive learning environment. The inhibiting factors found are students' difficulties in expressing ideas, differences in levels of understanding between students, and time constraints in the learning process.